A cone crusher model with a coupled energy- and breakage dependency. (1st October 2021) - Lindqvist, Mats; Li, Haijie
Highlights: The paper describes a method to predict the product particle size distribution (PSD) of a cone crusher. A previously developed energy mode that considers the entire size distribution, was applied to the calculated PSD. When operating at the minimum CSS, the crusher's specific energy consumption, as calculated by the energy model, must coincide with the crusher's available power divided by its tonnage at that CSS. This gives the minimum CSS that the crusher can operate at, and the corresponding PSD. Abstract: A cone crusher model is presented that uses the familiar "population balance" framework. The model was fitted so that the product particle size distribution can be predicted when operating at the minimum crusher gap CSS. A previously developed energy model is applied to the particle size distribution that is the output of the breakage model. This gives an estimate of the specific energy required, to generate that particle size distribution. The same quantity is calculated by dividing the crusher's available motor power by the tonnage at range of different CSS's assuming each of these are the minimum. The CSS that gives the same specific energy consumption as calculated by these two different techniques, corresponds to the minimum CSS that the crusher can reach. While the modeling approach is sound and gives realistic results, further validation against full scale test data is needed.